Peran Proram KKN dalam Pengembangan Literasi dan Numerasi Siswa Sekolah Dasar pada Wilayah Terpencil: Studi Kasus di SD N 040481 Desa Cinta Rakyat - Khairuddin Tambusai; Afdal Hafiz Takar; Amaliza Khaira; Raya Mahfuzah; Muhammad Wahid Daulay; Tri Suci Irawan (SEWAGATI: Jurnal Pengabdian Masyarakat Indonesia, 2025)
The Community Service Program (KKN) in Cinta Rakyat Village plays a strategic role in improving literacy and numeracy skills among elementary school students in remote areas that face limitations in teaching staff, learning media, and family support. The program is carried out over four weeks with three meetings per week, where university students apply participatory and contextual learning approaches to create an active, enjoyable, and easy-to-understand learning atmosphere. By using creative media such as picture books, educational games, number cards, and simple visual aids, the learning activities are designed to strengthen basic reading, writing, and arithmetic skills according to students’ cognitive development levels. Evaluation results show significant improvements in reading fluency, text comprehension, and basic numerical operations, along with increased motivation and self-confidence. In addition to benefiting students, the program also engages teachers and parents in supporting learning activities, creating positive collaboration between schools, students, and the community. Overall, the KKN program in Cinta Rakyat Village serves as a good practice model for addressing educational disparities, promoting equal access to quality basic education, and raising collective awareness of the importance of education in advancing remote areas of Indonesia.